Inflammatory bowel disease in families with four or more affected first-degree relatives. (2nd January 2023) - Boaz, Elad; Bar-Gil Shitrit, Ariella; Schechter, Menachem; Goldin, Eran; Reissman, Petachia; Yellinek, Shlomo; Koslowsky, Benjamin
Abstract: Background: Family history increases the risk for inflammatory bowel diseases (IBDs). However, data on differences in phenotypic characteristics among patients with a strong family history of IBD are scarce and controversial. The aim of the study was to compare the phenotypic features of IBD patients with four or more affected first-degree relatives with sporadic cases of IBD. Methods: Patients with familial and sporadic IBD were identified from the institutional IBD database. IBD patients from families with at least four first-degree affected relatives were selected for analysis and were compared to non-matched sporadic cases with IBD chosen randomly. Comparison for type of IBD (Crohn's disease (CD) vs. ulcerative colitis (UC)), age at onset as well as for disease extent, behavior, extraintestinal manifestations and indicators of severe disease were analyzed. Results: Thirty-five patients with familial IBD (28 CD, seven UC) were compared to 88 sporadic IBD patients (61 CD, 24 UC and three IBDU). Disease duration was 10.3 ± 8.2 in the familial and 8.0 ± 7.2 years in the sporadic cases, p =.13. The familial cases were younger at diagnosis (19.3 ± 8.6 vs. 25.7 ± 11.8, p =.004). Patients with familial compared to sporadic IBD were significantly more likely to require steroid treatment (80% vs. 54.5%, p =.009), biological treatment (94.3%, vs. 63.6%, p <.001) or surgery (25.7%, vs. 11.4%, p =.048). Conclusions: IBD with a very strong positive family history is associated with younger age at onset and a more adverse IBD phenotype compared to sporadic IBD.